PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BAPPEDA KABUPATEN WONOSOBO TAHUN 2013 - Ary Sutrischastini; Ratna Setyani (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2014)
This research goal is to identification and evaluation influence of work motivation and work environment to employee’s performance in BAPPEDA Kabupaten Wonosobo. The object of this research is 37 employees of Badan Perencanaan Pembangunan Kabupaten Wonosobo. And the location of this research is at Badan Perencanaan Pembangunan Kabupaten Wonosobo. The analysis used is test validity, reliability testing, and test the hypothesis, with the help of the computer program SPSS version 17, using multiple linear regression analysis. Based on calculations of data and analysis used, the regression equation is obtained: Y = 11.733 + 0.320 X1 +0.334 X2 + ε, by using the equation regression analytical method can conclude that (X1) take effect positively against employees performance. With t value in amount of 2,219 (bigger than t in table in amount of 1,690) and significance value in amount of 0,33. By applying significance limited value in amount of 0,05, it means, hypothesis that claim if work motivation take effect against employees performance can be accepted. There is a positive and significant correlation between work environment variables (X2) against employees. With t value in amount of 2,219 (bigger than t in table in amount of 1,690) and significance value in amount of 0,33 (smaller than 0,5). Simultaneously, work motivation take effect positively and significantly against employees performance with the F value in amount of 11,562 (bigger than 0.05), then obtained significance value 0.000. It can be concluded that the work motivation and work environment has a positive and significant influence on employee performance in BAPPEDA Kabupaten Wonosobo.